Google Map API service for VRP Solving Application - Satyananda, Darmawan (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami), 2017)
Computer program application was widely used to solve VRP (Vehicle Routing Problem) cases. In general, the graph used was mainly to model the problem, instead of depicted actual geographic condition. This modeling was inadequate to give comprehensive information to the users, particulary information related to real distance and real route. Google Map provided geographic data in the form of API (Application Programming Interface) that could be accessed by a computer program. Some of services provided were to display map, to access geographical data, distance of some places in distance matrix form, route from selected source to selected destination, and some more. This article studied developing web-based application for solving VRP using Google Map service. VRP variant implemented in the application is CVRP, and routing strategy used was Sequential Insertion method. Distance among customers was obtained from Google Map service, based on user input on the displayed map, as well as route drawing that used Google Map service. The application provided better visualization to the users, and route produced was more appropriate to the real circumstances. Test showed that length of the route is slightly longer than calculation from CVRP in general, which considered that route between two nodes is symmetrical.